Vision on biodiversity: Indigenous techniques of biodiversity assessment of butterflies in some forests of Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2022)
In the present study few indigenous techniques of the biodiversity assessment of butterflies were practiced in some forest ecosystems of Bangladesh. Butterfly-plant interaction in a forest ecosystem is a dynamic key factor that determines the status of a forest. A research team of the Environmental Biology and Biodiversity Laboratory (EBBL) of the department of Zoology, Dhaka University worked successfully on a population census of butterflies in some forests by using their newly innovated method the “Biotic-epicntre technical model”. This method deals with two important points for practicing it in the field condition. These are ethological aspects of the butterflies and application of epicentre-spot-design. In total 202 butterfly species (belonging to seven different families) were studied in the forests experimental stations of Bangladesh. The families are Hesperiidae, Papilionidae, Nymphalidae, Pieridae, Danaidae, Lycaenidae and Satyridae. The „vulnerability status‟ comprises„Available (Av)‟, „Rare (Rr)‟, „Near Threatened (Nt)‟, „Threatened (Tr)‟, „Critically Threatened (Ct)‟ and „Endangered (En)‟. The study revealed that the highest number of host-plant families (25 families) was used by lycaenids (45 species). The family Satyridae had the lowest number hostplant families (only 2). The second highest number of host-plant families (24 families) was associated with the family Nymphalidae (34 butterfly species). 38 butterfly species of Hesperiidae were associated with only nine families of the host-plants. The family Papilionidae (19 species) was related to only five host plant families. The butterflies (23 species) of the family Pieridae were found to depend on ten host-plant families. The members of the family Danaidae (12 species) were found on four host-plant families. More than 35 forest-areas of Bangladesh were included in the present investigation. Out of the total studied species (202), six species were found and declared „Endangered‟. Among the examined butterflies, 12, 13, 9, 64 and 98 species hold the status of Critically Threatened, Threatened, Near Threatened, Rare and Available respectively. The population census of the butterflies was carried out in three major forest areas of Bangladesh. The biodiversity assessment methods practiced in the various experimental fields have been illustrated with their respective different figures.J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(1): 1-14